Credit Reversals - Vazquez, Francisco (Washington, D.C. : International Monetary Fund, 2021)
This paper studies episodes in which aggregate bank credit contracts alongside expanding economic activity-credit reversals. Using data for 179 countries during 1960-2017, the paper finds that reversals are a relatively common phenomenon--on average, they occur every five years. By comparison, banking crises take place every eight years on average. Credit reversals and banking crises also appear related to each other: reversals become more likely in the aftermath of banking crises, while the likelihood of crises drops following reversals. In terms of foregone economic activity, reversals are shown to be very costly, at about two-thirds of the costs of banking crises after taking into account their relative frequencies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Financial Crises; Foreign Exchange; Informal Economy; Monetary Policy, Central Banking, and The Supply Of Money; Underground Econom